THE EFFECT OF PRODUCT QUALITY AND QRIS PAYMENT AS A MODERATING VARIABLE ON REPURCHASE DECISION - Sutarman, Mohamad Anwar; Rombe, Elimawaty; Ponirin (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
This study aims to determine whether product quality affects repurchase decisions, whether the availability of QRIS payment methods affects repurchase decisions, and whether the availability of QRIS payment methods influences the relationship between product quality and repurchase decisions. The method used in this research is quantitative, using an accidental sampling technique. Each construct in this study was evaluated using a 5-point Likert scale and analyzed using the PLS-SEM instrument. The result of this study is that H1, the variable of product quality (X), has a significant impact on the repurchase decision at the Banuia Momberata Poso cafe. The result is confirmed based on the t-statistic value of 2.578 > 1.96 with a p-value of 0.010 < 0.05. H2: The variability of the QRIS payment method (M) does not affect the repurchase decision at the Poso Banuia Momberata cafe. This can be proven by looking at the t-statistic value of 1.426 < 1.96 and the p-value of 0.154 > 0.05, H3 variable besar. 0.05, H3: QRIS payment method availability variable (M) does not moderate the effect of product quality (X) on the latent dependent variable, the repurchase decision, in Banuia Momberata Poso Cafe. This can be demonstrated by the t-statistic value of 1.188 < 1.96 and the p-value of 0.235 > 0.05.